2020
DOI: 10.1088/1367-2630/ab8262
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement area law for shallow and deep quantum neural network states

Abstract: A study of the artificial neural network representation of quantum many-body states is presented. The locality and entanglement properties of states for shallow and deep quantum neural networks are investigated in detail. By introducing the notion of local quasi-product states, for which the locally connected shallow feed-forward neural network states and restricted Boltzmann machine states are special cases, we show that Rényi entanglement entropies of all these states obey the entanglement area law. Besides,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
(92 reference statements)
0
11
0
Order By: Relevance
“…Because by construction our ansatz represents a product of terms with local support, it can be seen as an effective implementation of a quasi-product states introduced in [22]. This suggests that the entanglement entropy of the state can obey at most an area law.…”
Section: Physical Properties Of the Gnn Ansatzmentioning
confidence: 99%
“…Because by construction our ansatz represents a product of terms with local support, it can be seen as an effective implementation of a quasi-product states introduced in [22]. This suggests that the entanglement entropy of the state can obey at most an area law.…”
Section: Physical Properties Of the Gnn Ansatzmentioning
confidence: 99%
“…For one-dimensional many-body states, two thoroughly studied, popular but different structures exist-multiscale entanglement renormalization ansatz (MERA) [36] and matrix product states (MPS) [37], of which the EE scales with the subsystem size or not at all, respectively [35]. For most pertinent studies, MPS has been proven to be efficient enough to be applicable to a variety of tasks [38][39][40][41]. However, our experiments show that, regarding our entanglement-structured design of the new tensorized LSTM architecture, LSTM-MERA performs even better than LSTM-MPS in general without increasing the number of parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in this paper, we consider a neural-network inspired variational Ansatz for the quantum wave function [44]. Machine learning techniques have been proved fruitful to the field of many-body quantum physics [44][45][46][47][48][49][50][51][52][53][54][55]. Specifically, exciting progress has been made in identifying quantum phases and transitions among them, either symmetry-broken phases [47][48][49][50]56] or topological phases [57], establishing connections to renormalization group techniques [58,59] and perturbation theory [60].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, machine learning ideas have also been used in measuring quantum entanglement and wave function tomography [55,61,62]. We focus on a particular neural network variational state, referred to as restricted Boltzmann machines (RBM) quantum states which have been proven [54,63] to capture both an area-law as well as volume-law worth of entanglement depending on the locality of the neural network. In addition, recent work [52] showed that RBM states can also be used to parametrize quantum wave functions with non-Abelian symmetries.…”
Section: Introductionmentioning
confidence: 99%